2012
DOI: 10.1002/jqs.2597
|View full text |Cite
|
Sign up to set email alerts
|

Two paleoecological histories spanning the period of human settlement in southeastern Brazil

Abstract: The absence of human occupation sites in southeastern Brazil during the mid Holocene has been referred to as the 'Archaic Gap' (8970-1940 cal. a BP) and is predicted to have resulted from increased aridity. A ca. 14 000 cal. a pollen history from two well-dated lake sediment cores located within the archeological district of Lagoa Santa, in the State of Minas Gerais, southeastern Brazil, was used to test this hypothesis. Our analyses indicated that the present cerrado and tropical semi-deciduous forest mosaic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 32 publications
0
18
0
6
Order By: Relevance
“…Although Euclidean distances between sites are similar between 60–49 k BP and modern times, the older period may have offered more connectivity than under modern conditions. Human actions throughout the late glacial and the Holocene have caused megafaunal extinction (Raczka et al, ), habitat fragmentation and altered fire regimes (Raczka et al, ); all of which limit species movement. Many forest‐dwelling animals require forest cover or a complexity of habitat structure rather than a particular composition of plant species (Lawton et al, ; MacArthur & MacArthur, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Euclidean distances between sites are similar between 60–49 k BP and modern times, the older period may have offered more connectivity than under modern conditions. Human actions throughout the late glacial and the Holocene have caused megafaunal extinction (Raczka et al, ), habitat fragmentation and altered fire regimes (Raczka et al, ); all of which limit species movement. Many forest‐dwelling animals require forest cover or a complexity of habitat structure rather than a particular composition of plant species (Lawton et al, ; MacArthur & MacArthur, ).…”
Section: Discussionmentioning
confidence: 99%
“…The combined DCA of both Serra Negra and Colônia showed that forested samples (<50% Poaceae) from both sites were spread across Axis 1 and tended to be located on the positive end of Axis 2 (Figure 7). (Raczka et al, 2018), habitat fragmentation and altered fire regimes (Raczka et al, 2013); all of which limit species movement. Many forest-dwelling animals require forest cover or a complexity of habitat structure rather than a particular composition of plant species (Lawton et al, 1998;MacArthur & MacArthur, 1961).…”
Section: Ecological Similarity As a Metric Of Landscape Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…A partir dos objetivos do projeto, fica claro que há um esforço de rompimento das barreiras disciplinares dos campos da biologia, da arqueologia e da antropologia. Entre as principais contribuições do projeto pode-se destacar 7 : 1) humanos e megafauna conviveram na região, porém não há evidencia de utilização de derivados desses animais em sítios arqueológicos Piló, 2003;Hubbe et al, 2013); 2) os primeiros habitantes da região ocuparam locais em campo aberto, além das grutas e abrigos, porém não foram encontradas ocupações arqueológicas no Pleistoceno (Bueno, 2012); 3) o modelo biológico de ocupação do continente proposto por Neves e colegas foi corroborado usando evidências adicionais de 30 novos esqueletos humanos (Neves et al, 2014); 4) estudos de paleoclima mostraram aumento de umidade no Holoceno Inicial, concordando com o início das ocupações em Lagoa Santa, e aumento de aridez ou instabilidade climática no Holoceno Médio, em acordo com a diminuição das ocupações humanas na região (Araujo et al, 2013;Raczka et al, 2013).…”
Section: O Retorno à Lagoa Santa: O Projeto 'Origens'unclassified
“…Salgado-Labouriau, 1997;Ledru, 2002;Meyer et al, 2014), there are few records and little knowledge of the history of these changes. The majority of the available information comes from palynological studies that have been performed in lakes and in the palm swamps of the Cerrado core area (Ledru, 1993;Behling, 1995Behling, , 2002Behling, , 2003Ferraz-Vicentini and Salgado-Labouriau, 1996;Parizzi et al, 1998;Barberi et al, 2000;Horák, 2009;Lorente et al, 2010;Raczka et al, 2012;Cassino and Meyer, 2013).…”
Section: Introductionmentioning
confidence: 98%